Selection Criteria and Suggestions for the Use of Lumber as Building Material - Cuevas D., Héctor R. (Bosque (Valdivia), 1988)
A method to select types of lumber suitable as building material in Chile, is presented. The selection procedure is based upon: dimensional stability, natural durability and surface behavoir. Suggested theoretical moisture content and construction precautions are presented. General recomendations for using lumber as building material are also stated.